2007
DOI: 10.1016/j.jbiomech.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent deformations in bone cells exposed to fluid flow in vitro: investigating the role of cellular deformation in fluid flow-induced signaling

Abstract: Numerous experiments have shown fluid flow to be a potent stimulator of bone cells in vitro, suggesting that fluid flow is an important physical signal in bone mechanotransduction. In fluid flow experiments, bone cells are exposed to both time-dependent (e.g. oscillating or pulsing) and timeindependent (e.g. steady) flow profiles. Interestingly, the signaling response of bone cells shows dependence on loading frequency and/or rate that has been postulated to be due to viscoelastic behavior. Thus, the objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…However, these studies are generally constrained to a limited set of candidate genes or proteins as part of known or suspected signaling pathways. Osteocytic cells elastically deform when subject to physiological peak fluid shear stresses up to 5 Pa (Kwon and Jacobs, 2007; Price et al, 2011), initiating the rapid release of adenosine triphosphate (ATP) and prostaglandin E 2 via gap junctions or hemichannels (Batra et al, 2012; Cherian et al, 2005; Genetos et al, 2007; Klein-Nulend et al, 1995). In turn, these factors contribute to cell network propagation of intracellular calcium waves in proportion to flow-induced shear stress in vitro (Huo et al, 2008; Lu et al, 2012) as well as during in situ dynamic bone loading (Jing et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are generally constrained to a limited set of candidate genes or proteins as part of known or suspected signaling pathways. Osteocytic cells elastically deform when subject to physiological peak fluid shear stresses up to 5 Pa (Kwon and Jacobs, 2007; Price et al, 2011), initiating the rapid release of adenosine triphosphate (ATP) and prostaglandin E 2 via gap junctions or hemichannels (Batra et al, 2012; Cherian et al, 2005; Genetos et al, 2007; Klein-Nulend et al, 1995). In turn, these factors contribute to cell network propagation of intracellular calcium waves in proportion to flow-induced shear stress in vitro (Huo et al, 2008; Lu et al, 2012) as well as during in situ dynamic bone loading (Jing et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the pore size of the cytoplasm is around tens of nm [39], and particles of comparable or larger size are trapped in the cytoskeletal structure and do not undergo diffusive motion. In a previous study to characterize flow-induced deformation in bone cells, the displacements of cellbound microbeads were measured [40], where the cells were attached to a fibronectin-coated quartz slide. These previous studies, and the effect of particle size on deformation measurements reported in this work, confirm that microbead movement in the cell during cell deformation closely reflects cytoplasmic deformation in a short time interval.…”
Section: Discussionmentioning
confidence: 99%
“…understanding how cellular mechanotransduction occurs. 19,23 Other studies have suggested that in addition to maintaining the cell's mechanical integrity, the cytoskeleton plays a central role in sensing mechanical stimuli. 26,28,29 Nevertheless, the role of mechanical tension in the cytoskeleton in bone cell mechanotransduction, as distinguished from the existence of an intact cytoskeleton itself.…”
Section: Discussionmentioning
confidence: 99%